Development of an IoT-based Soil Nutrient Monitoring and GIS Mapping System for Precision Agriculture - Asrul Abdullah; Eka Indah Raharjo; Muhammad Iwan; Rizki Faizal; Maryogi (Advance Sustainable Science Engineering and Technology, 2025)
Agriculture is a field that contributes to Indonesia's economic development.  Unpredictable weather, temperature fluctuations, and the difficulty in assessing soil quality hinder farmers in enhancing crop productivity. The IoT in signifies a beneficial progression that will assist farmers in their endeavors. Precision agriculture is an innovative approach that employs information technology for sustainable agricultural management. This research aims to assess soil nutrients and provide mapping data based on the evaluated agrarian sites. The testing sites are situated in three sub-districts within Kubu Raya Regency: Sungai Kakap, Ambawang, and Rasau Jaya. The soil study indicated a temperature range of 29.40 °C to 36.80 °C. Soil moisture varied from 4 % to 89.10 %. The soil pH varied between 6.90-8.07 PH. The soil salinity was rather modest. Nutrient levels, particularly nitrogen, were slightly lower than those of phosphate and potassium, necessitating fertilizer use to enhance plant vegetative development. Incorporating the Internet of Things onto agricultural land delivers data as real-time monitoring, which will be essential for improving agricultural output. This scalable method mitigates contemporary agricultural difficulties by diminishing environmental impact and enhancing crop resilience. This study facilitates sustainable, intelligent agricultural techniques to address the escalating needs of a swiftly expanding global population.